AKTIVITAS ANTIHIPERGLIKEMIA EKSTRAK AIR DAN HEKSANA DAUN PANDAN WANGI (Pandanus amaryllifolius) TERHADAP TIKUS PUTIH (Rattus novergicus) - Sitaresmi Yuningtyas; Siti Mariam; Auliatun Nisa (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2017)
Diabetes mellitus is a disorder of carbohydrate metabolism characterized by high blood glucose levels, or hyperglycemia. Hyperglycemia is a condition where the amount of glucose in the blood exceeds normal limits. Many plants that have the potential as the lowering of blood glucose levels, one of which pandan leaves (Pandanus amaryllifolius). The purpose this study were to identified class of chemicals compounds contained in extracts of water and hexane pandan leaves. Beside that, this study was conducted to determine the activity extracts of water and hexane pandan leaves to decrease blood glucose levels of white rats (Rattus novergicus) with hyperglycemia. Simplicia of pandan leaves extracted by maceration method. Condensed extract contains compounds defined and tested in vivo in rats induced by alloxan. Water extract of pandan leaves (EADP) contained alkaloids, flavonoids, saponins and tannins. Hexane extract of pandan leaves (EHDP) contained alkaloids and steroids. Measurement of blood glucose levels were measured by using a glucometer for 15 days with intervals in every 3 days. Negative control treatment with Na-CMC 1% was increased in blood glucose levels to 137.50%. Metfomin as positive control treatment with 9 mg could decrease the blood glucose levels to 66.41%. Treatment with EADP 300, EADP 600, EHDP 300 and EHDP 600 could decrease glucose levels 42.38, 60.25, 26.99 and 24.81% respectively. Therefore, water and hexane extracts of pandan leaves (Pandanus amaryllifolius) could decrease the blood glucose levels with in vivo.